2019
DOI: 10.1016/j.cej.2019.122229
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intensification of direct acetate cleavage and CO2 reduction to generate methane by bioaugmentation and increased electron transfer

Abstract: Detailed analysis of multiple methane production pathways was conducted.• Maximum H 2 production was promoted by ∼3 and 4 times with bioaugmentation and CMs.• Acetoclastic methanogenesis was beneficial from both bioaugmentation and CMs.• Various CH 4 generation pathways were stimulated by CMs except for DIET-dependent CO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…More importantly, conductive materials further facilitated the completion of this process. It was also observed that conductive materials increased the proportion of acetoclastic methanogenesis in anaerobic granular sludge [49]. Overall, the two methods, inhibitor and natural abundance stable isotope fractionation, reached perfectly consistent conclusions.…”
Section: Carbon Stable Isotope Fractionation and Calculation Confirmementioning
confidence: 51%
“…More importantly, conductive materials further facilitated the completion of this process. It was also observed that conductive materials increased the proportion of acetoclastic methanogenesis in anaerobic granular sludge [49]. Overall, the two methods, inhibitor and natural abundance stable isotope fractionation, reached perfectly consistent conclusions.…”
Section: Carbon Stable Isotope Fractionation and Calculation Confirmementioning
confidence: 51%
“…However, in H 2 upgrading/ammonia inhibited AD system, methane production is mainly from hydrogenotrophic methanogenesis pathway. For acetoclastic methanogenesis, methanogens oxidize carboxyl groups to CO 2 and generate reducing forces to reduce methyl carbon to methane ( Welte and Deppenmeier, 2014 ; Xiao et al, 2019b , 2020a ). At present, only Methanosarcina and Methanosaeta have been found to produce methane by acetoclastic methanogenesis ( Holmes and Smith, 2016 ; Li et al, 2018 ; Xiao et al, 2019a ).…”
Section: Effects Of Antibiotics On Anaerobic Digestionmentioning
confidence: 99%
“…Methanogens are a class of exclusive anaerobic archaea that are widely distributed and can survive in lakes, marshes, sludges, wetlands, rice paddy soils, inside organisms, and even extreme environments ( Xiao et al, 2017 , 2019b , c ; Conrad, 2020 ). The blocking of the methanogenic reaction leads to the accumulation of organic acids, and the upstream acidification reaction will be slowed down by product inhibition.…”
Section: Effects Of Antibiotics On Anaerobic Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas sample (200 lL) was taken from the headspace using a sterilized syringe with a two-way valve. Methane and CO 2 were analyzed by gas chromatography (GC; Agilent 7820A, USA) equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD) as previously described (Xiao et al, 2019b). The column temperature was 80°C, and the low detection limits for methane and CO 2 were approximately 0.0008 mM and 0.04 mM, respectively.…”
Section: Methane Oxidation Ability Under Wet and Dry Conditionsmentioning
confidence: 99%